Exposure to ultraviolet B radiation or oral supplementation with vitamin D and calcium in leopard geckos: beneficial or not? - Franco, Francisco; Patrício, Rui; Faustino, Ana (Revista de Ciência Veterinária e Saúde Pública, 2024)
Vitamin D regulates many fundamental physiologic functions in vertebrates, mainly calcium homeostasis. Because of the diversity of reptile species and the various environmental adaptations, many studies have been conducted to understand the individual needs and adaptations of each specie regarding vitamin D, its importance and acquisition in the wild. This study aimed to evaluate the influence of exposure to ultraviolet (UV) radiation or vitamin D and calcium oral supplementation on plasma levels of ionized calcium in Eublepharis macularius (Leopard gecko). Blood samples were collected from the jugular vein in two check-up appointments five weeks apart and the concentration of ionized calcium (iCa++) was analyzed in 15 Leopard geckos from different owners and submitted to different environmental conditions: supplemented animals (n = 5), animals exposed to UV radiation (n = 5) and animals not supplemented or exposed to radiation (control) (n = 5). iCa++ plasma levels did not vary significantly (p>0.05) among groups, or within each group during the study. The Leopard gecko has the ability to maintain iCa++ concentration, without any supplementation, for at least 42 days, and the supplemented animals seem not to have benefited from supplementation during this period of time.